Hybrid cyber security of unmanned aerial vehicles - DÖŞ, Orhun; KARAKOCA, Yunus Emre; CAMADAN, Ebutalha; BAYKALI, Fikret (International Journal of Applied Methods in Electronics and Computers, 2023)
Unmanned aerial vehicle technological improvement has had a direct influence on today’s warfare. As today’s battles take place in cities, the distinction between civilians and soldiers has grown increasingly hazy. There is a wealth of literature on autonomy and ethical concerns concerning autonomous weapon systems. Unmanned aerial vehicles must contend with a slew of security risks, ranging from electronic jammers to missile strikes. The societal acceptance of these techniques, ethical value judgments, and long-term consequences are all important topics to discuss. Unmanned aerial vehicles have a wide range of applications in the military, from gathering intelligence to destroying targets, and in the civilian arena, from agriculture to photography. Furthermore, unmanned aerial vehicles have the potential to be used not just for military or commercial goals, but also for international crimes. Nowadays unmanned aerial vehicles are used in electronic warfare to monitor enemy positions, prevent their communications by jamming systems, instantly monitor the country’s border security, render the electronic systems of the determined targets inoperable, and listen for information via communication systems. Under the conditions specified above, the study seeks to provide a hybrid approach to unmanned aerial vehicles. The cybersecurity of unmanned aerial vehicles, software security, physical security, and social and cultural security will all be handled from a single point of view.